Rough surface preparation through chemical etching for super-hydrophobicity / Aisswarya Kumaran - Aisswarya, Kumaran (2016)
Super-hydrophobic films with water contact angle higher than 150° have been the subject of great interest and enthusiastic study in recent years. These films are fabricated by incorporating appropriate surface roughness with surfaces of low surface energy. The interest in surfaces with self-cleaning ability is being driven by its various applications. In this project, superhydrophobic surface was produced through chemical etching process using myristic acid and ethanol solution of hydrochloric acid. Few parameters, namely etching time, myristic acid concentration, type of aluminium substrate in terms of thickness and reaction temperature were manipulated to determine which is optimum. The resultant contact angle was measured using an optical angle meter to determine if the superhydrophobic state has been achieved. The surface morphology and chemical composition was examined using SEM and EDS respectively. Subsequently, the highest contact angle achieved was 159.4º±1.1º. The end-product surface showed micro-nano morphology, which is a significant characteristic of superhydrophobic surface. EDS results indicated the formation of aluminium palmitate due to the bonding between tetradecanoate ion, CH3(CH2)12COO- with the Al3+ on the aluminium surface. Calculations revealed that 95.2% of the surface area is made up of solid-air interface, implying that only 4.8% of the surface is in contact with the water droplet. This method for fabrication of superhydrophobic surface can be used for large-scale fabrication of superhydrophobic Al surfaces as technique is low-cost, quick and simple to adopt.